2000
DOI: 10.1152/ajpheart.2000.279.6.h2797
|View full text |Cite
|
Sign up to set email alerts
|

Renin-angiotensin system and sympathetic nervous system in cardiac pressure-overload hypertrophy

Abstract: Angiotensin II and norepinephrine (NE) have been implicated in the neurohumoral response to pressure overload and the development of left ventricular hypertrophy. The purpose of this study was to determine the temporal sequence for activation of the renin-angiotensin and sympathetic nervous systems in the rat after 3-60 days of pressure overload induced by aortic constriction. Initially on pressure overload, there was transient activation of the systemic renin-angiotensin system coinciding with the appearance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 38 publications
4
49
0
5
Order By: Relevance
“…Although the adrenergic receptor blockers are widely used to prevent cardiac hypertrophy (25,26), the underlying mechanisms of their effect remain to be elucidated. It has also been reported that sympathetic activation plays a critical role in the pressure-overload rat model of abdominal aortic constriction (27,28). In this regard, adrenergic receptor blockade is likely to be an effective tool for the prevention of pressure overload-induced ventricular hypertrophy.…”
Section: Discussionmentioning
confidence: 96%
“…Although the adrenergic receptor blockers are widely used to prevent cardiac hypertrophy (25,26), the underlying mechanisms of their effect remain to be elucidated. It has also been reported that sympathetic activation plays a critical role in the pressure-overload rat model of abdominal aortic constriction (27,28). In this regard, adrenergic receptor blockade is likely to be an effective tool for the prevention of pressure overload-induced ventricular hypertrophy.…”
Section: Discussionmentioning
confidence: 96%
“…One of these is induction of AAS in rats, which leads to systemic hypertension, LV hypertrophy, and activation of the reninangiotensin-aldosterone system (1,3). Using a model of AASinduced cardiac hypertrophy, we assessed cardiac function, blood pressure, and LV hypertrophy in adult Sprague-Dawley rats.…”
Section: Discussionmentioning
confidence: 99%
“…25 After general anesthesia with intraperitoneal pentobarbital (60 mg/kg) and heparin (1500 U/kg), the heart from each rat was quickly extracted from the thoracic cavity, immersed in ice-cold Krebs buffer, and mounted onto a nonrecirculating heart-perfusion apparatus. Retrograde perfusion through the aorta was initiated with oxygenated Krebs buffer (in mmol/l: NaCl 128, potassium chloride (KCl) 4.8, KH 2 PO4 1.2, MgSO 4 1.2, NaHCO 3 25, dextrose 11, CaCl 2 1.6; EDTA 2 pmol/l; PaO 2 500-600 mm Hg; pH 7.4) and maintained at a constant temperature of 371C.…”
Section: Isolated Perfused Heartmentioning
confidence: 99%